East-West economic cooperation: Interests involved, institutional possibilities and economic rationale - Patricia Bauer (Intereconomics, 1995)
Beyond the existing forms of East-West cooperation in Europe such as economic assistance, loans, joint ventures and association agreements, both sides are looking for suitable ways of establishing more institutionalized relations. Already existing institutions, membership of which could be offered to the new market economies, are EFTA, the European Economic Area (EEA) and the EU. This article discusses the effects of membership for both eastern and western countries in the light of their differing interests.
Keywords: 330; System Transformation